Diversi terhadap Pelaku Pembuangan Orok Bayi oleh Anak (Studi Kasus Pengadilan Negeri Denpasar) - Ni Putu Lalitha Candra Laksmi; Anak Agung Sagung Laksmi Dewi; Diah Gayatri Sudibya (Jurnal Preferensi Hukum, 2021)
This journal is titled Diversion Against Actors Disposing Baby Orok by Children Like adults, children as perpetrators of crimes will also experience a legal process that is identical to adults who commit criminal acts, the meaning of identical words here means almost the same, different only time period and how to handle it. Diversion is the transfer or transfer of the judicial process into an alternative process of settlement of cases, namely through deliberations of recovery or mediation. The problem 1 what is the Judge's consideration for deciding Diversion on Children as Actors? And 2 what is the criminal sanction inflicted on children as perpetrators of criminal offenses by babies? The approach to the problem used in this study, this study uses a type of normative legal research called doctrinal legal research. The problem approach in this research is carried out by using the legislative approach method by examining all laws and regulations relating to the relevant legal events, conceptual approaches that move from the views and doctrines that develop in law, and case approach. Judge's consideration in determining the diversity of perpetrators of childbirth disposal by children, this case is found in case No. 18/Pid.SusAnak/2016/PN.Dps, children are given the opportunity to correct mistakes and be returned to their parents to be guarded and guided and to be fostered so that the child does not do the deed again.